Recent progress in nanotechnology-based novel drug delivery systems in designing of cisplatin for cancer therapy: an overview - Muhammad Asim Farooq; Md Aquib; Anum Farooq; Daulat Haleem Khan; Mily Bazezy Joelle Maviah; Mensura Sied Filli; Samuel Kesse; Kofi Oti Boakye-Yiadom; Rukhshona Mavlyanova; Amna Parveen; Bo Wang (Artificial Cells, Nanomedicine, and Biotechnology)
Cisplatin cis-(diammine)dichloridoplatinum(II) (CDDP) is the first platinum-based complex approved by the food and drug administration (FDA) of the United States (US). Cisplatin is the first line chemotherapeutic agent used alone or combined with radiations or other anti-cancer agents for a broad range of cancers such as lung, head and neck. Aroplatin™, Lipoplatin™ and SPI-077 are PEGylated liposome-based nano-formulations that are still under clinical trials. They have many limitations, for example, poor aqueous solubility, drug resistance and toxicities, which can be overcome by encapsulating the cisplatin in Nemours nanocarriers. The extensive literature from different electronic databases covers the different nano-delivery systems that are developed for cisplatin. This review critically emphasizes on the recent advancement, development, innovations and updated literature reported for different carrier systems for CDDP.